2010
DOI: 10.1016/j.ultsonch.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sonochemical degradation of bisphenol-A by bicarbonate ions

Abstract: Sonochemical elimination of organic pollutants can take place through two degradation pathways. Molecules with relatively large Henry's law constants will be incinerated inside the cavitation bubble, while nonvolatile molecules with low Henry's law constants will be oxidised by the OH(*) ejected from the bubble of cavitation. Taking bisphenol-A as a model pollutant, this study points out an alternate degradation route, mediated by bicarbonate ions, which is significant for the elimination of micro-pollutants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 31 publications
0
55
0
Order By: Relevance
“…It is well known that removal of organic pollutants depends on amounts of reactive species, with this, in turn, being dependent on the presence of additional substances in the reaction solution that can act as radical scavengers. Inorganic ions and organic substances are, in fact, well-known OH scavengers [30,31]. In a previous study [23], the ultrasonic degradation of bisphenol-A was also shown to be impacted upon negatively by humic acid.…”
Section: Resultsmentioning
confidence: 95%
“…It is well known that removal of organic pollutants depends on amounts of reactive species, with this, in turn, being dependent on the presence of additional substances in the reaction solution that can act as radical scavengers. Inorganic ions and organic substances are, in fact, well-known OH scavengers [30,31]. In a previous study [23], the ultrasonic degradation of bisphenol-A was also shown to be impacted upon negatively by humic acid.…”
Section: Resultsmentioning
confidence: 95%
“…Almost confluent cells were placed for 2 days in medium containing serum and then in serum-free medium for 2 h. Cells were then treated with 10 − 10 M T3 or 10 − 7 M T4 combined with the indicated amounts of BPA for the times indicated. Both the plastic experimental items and the water utilized to prepare the reagents were pretreated by the enhanced sonochemical degradation to reduce any potential background BPA (Pétrier et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…1) . , which, unlike the •OH, could migrate to the bulk solution and induced the degradation of the CBZ molecules [34,35]. However, excess HCO 3 -(150 and 200 mg· L -1 ) would also compete with CBZ molecules for •OH to form much less reactive inorganic radical species (Eq 6) [28], leading to the reduced degradation rate.…”
Section: Effect Of Inorganic Anionsmentioning
confidence: 99%